Composition, Diversity, and Habitat Association of Spider Species (Araneae) in Three Different Land Covers of Tangub City, Misamis Occidental, Philippines - Revilleza, Chen; Socias, Maria Elezairah; Zaragoza-Magsayo, Monaliza Joy; Rivera, Rodrin; Bullong, Lynde (Journal of Tropical Life Science, 2026)
Spiders are significant to ecosystems as they regulate insect populations, act as both predator and prey, and enhance biodiversity. This study examined the composition, diversity, and habitat association of spider species (Araneae) in the three different land covers of Tangub City, Misamis Occidental, Philippines. The samplings were particularly conducted in Barangay Banglay, predominantly an agricultural area, Barangay Hoyohoy, a mountainous terrain, and Barangay Caniangan, a riparian area. Transect walks and opportunistic sampling methods were used. 38 species belonging to 12 families under 27 genera were identified from the 782 individuals captured, of which 2 species were endemic and 36 non-endemics. The three sampling areas attained moderate diversity, ranging from 2.17 to 2.66, with Banglay ranking the highest. Furthermore, Banglay and Hoyohoy showed a higher similarity index value of 0.68, indicating a higher number of shared spider species, accounting for 16 species. The Canonical Correspondence Analysis (CCA) across sampling areas illustrated axis 1 as the primary ecological gradient influencing spider abundance and distribution, with eigenvalues ranging from 0.05 to 0.11. In Banglay, Herennia multipuncta and Arachnura melanura were strongly associated with both relative humidity and air temperature. In Hoyohoy, Neoscona sp. and Camaricus sp. prefer higher air temperature, while species such as Nephila pilipes, Nephila kuhlii, Nephilengys malabarensis, Gnathopalystes sp., Poltys sp., Cheiracanthium sp., and Leucauge decorata are highly influenced by relative humidity. And in Caniangan, species such as Nephila pilipes, Gasteracantha sp., and Thomisus labefactus, are closely associated with warmer microclimatic environments, whereas taxa such as Leucauge fastigata and Heteropoda venatoria prefer more humid conditions. However, low eigenvalues suggest that the measured environmental variables have minimal effect on spider species, and other factors may play a more significant role. Key threats include habitat degradation across all sampling areas. The study recommends implementing targeted conservation measures and enforcing policies to preserve the integrity of the areas and protect the spider populations.